IMPLEMENTASI PEMBELAJARAN DENGAN METODE MULTISENSORI DALAM MENINGKATKAN KETERLIBATAN SISWA KELAS RENDAH SD - Ananda, Regina Dea; Zakiah, Linda; Sakmal, Juhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores how the multisensory method is used in lower grade primary schools to boost student engagement. Early grade students learn best through concrete experiences seeing, hearing, touching, and moving. Through a literature review of journals from 2020-2025, the study found that this method helps students be more active and emotionally connected during lessons. It also supports children with learning difficulties like dyslexia. Still, its success depends on the teacher’s ability to design suitable and engaging activities.